BSS518: Fundamental Research Methodology / College of Built Environment - UiTM, College of Built Environment (2015)
The course provides the student with the basic competencies to plan, conduct and analyse the research undertaking on a topic relevant to the construction industry. The competencies include what issues to consider when choosing research subjects, identifying research problems, how to use library sources to unearth the relevant literature, how to construct questionnaires and conduct surveys, how to select research design and use statistical or non-statistical data analysis technique, discuss the findings, and provide a written report of the research conducted. This will help students to improve in term of conceptual, analytical, decision making and problem solving, and communication skills.